Sintesis dan Karakterisasi Lempung Magnetik (Mg/Al-Fe Hydrotalcite) serta Aplikasinya Sebagai Adsorben Asam Fulvat - Saputro, Irwan Agung; Karmanto, Karmanto (ALKIMIA, 2019)
Synthesis of magnetic clay (Mg / Al-Fe Hydrotalcite) and its application as fulvic acidadsorbent has been carried out. Mg / Al-Fe Hydrotalcite was synthesized by reactingFeCl2.6H2O and FeSO4.7H2O (1: 1) solutions with Mg (NO3)2.6H2O and Al (NO3)3.9H2O (2:1) using the coprecipitation method simultaneously at pH intervals 10-13. Synthesis studiesinclude the study of the characteristics of solids synthesized using X-ray diffractometer andFTIR spectrometers, Mg / Al-Fe Hydrotalcite magnetism test using an external magnetic fieldand Mg / Al-Fe Hydrotalcite stability test in various medium pH. Fulvic acid was isolatedusing methanol solution and characterized using FTIR spectroscopy. The study of fulvic acidadsorption and desortion was studied by studying the fulvic acid adsorption kinetics by Mg /Al-Fe Hydrotalcite and the effect of time on the concentrated fulvic acid concentration of Mg/ Al-Fe Hydrotalcite.The characterization results showed the characteristics of the peak and the functionalgroup Mg / Al-Fe Hydrotalcite in X-ray diffractogram and FTIR spectra. The stability of Mg /Al-Fe Hydrotalcite tends to be stable at pH above 3. Based on FTIR spectra data, Telukpanjifulvic acid has the main functional groups namely -COOH (aliphatic and aromatic) andphenoh-OH groups. The results of the adsorption pattern of fuvic acid by Mg / Al-FeHydrotalcite are first order reaction kinetics that reach equilibrium with a reaction rateconstant (k1) of 24 x 10-4 minutes-1. The results of post-adsorption characterization showedthat fulvic acid entered into the inter-layer of Mg / Al-Fe Hydrotalcite as evidenced by theincrease in basal spacing prices in d003 which is a characteristic of hydrotalcite. Theinfluence of time on the concentrated fulvic acid concentration showed that the fulvic acidcould be desorbed from Mg / Al-Fe Hydrotalcite by 82.83% or 18.52 mg / L from a totalconcentration of 22.3556 mg / L.